Cerebrovascular disease : 22nd Princeton Conference - Chan, Pak H. (Cambridge University Press, 2002)
Arising from 22nd Princeton Conference on Cerebrovascular Disease, this text covers the current status and future directions of stroke pathophysiology, diagnosis and treatment. Available in both print and online formats, this survey of the basic and clinical science of stroke is essential reading for all involved in cerebrovascular disease.